Structural Compactness in Hen Egg White Lysozyme Induced by Bisphenol S: A Spectroscopic and Molecular Dynamics Simulation Approach. Issue 17 (20th July 2021) - Pramanik, Ushasi; Kongasseri, Anju Ajayan; Shekhar, Shashi; Mathew, Ashwin; Yadav, Rahul; Mukherjee, Saptarshi
Abstract: The endocrine disrupting compound Bisphenol and its analogues are widely used in food packaging products and can cause serious health hazards. The protein, Lysozyme (Lyz), showing anti‐microbial properties, is used as a "natural" food and dairy preservative. Herein, we explored the interaction between Lyz and Bisphenol S (BPS) by multi‐spectroscopic and theoretical approaches. Lyz interacts with BPS through static quenching, where hydrophobic force governed the underlying interaction. Molecular docking results reveal that tryptophan plays a vital role in binding, corroborated well with near UV‐CD studies. A decrease in the radius of gyration (from 1.43 nm to 1.35 nm) of Lyz substantiates the compactness of the protein conformation owing to such an interaction. This structural alteration experienced by Lyz may alter its functional properties as a food preservative. Consequently, this can degrade the quality of the food products and thereby lead to severe health issues. Abstract : Quenching in tryptophan fluorescence intensity of lysozyme upon interaction with the endocrine disruptor, Bisphenol S, is reported. Spectroscopic and molecular dynamics studies indicate that the Lysozyme experiences structural compactness due to interaction with Bisphenol S. The Ramachandran Plot predicts Bisphenol S induced modification in the secondary structure of lysozyme.